2022
DOI: 10.3390/atmos13020353
|View full text |Cite
|
Sign up to set email alerts
|

Response of Potential Evapotranspiration to Warming and Wetting in Northwest China

Abstract: In the last few decades, the climate in Northwest China has exhibited a warming–wetting tendency, which has been particularly prominent since the beginning of the 21st century. In this context, we analyzed the change in potential evapotranspiration (PET)in the corresponding period and its response to warming and wetting, which revealed clear periodic changes. The most significant changes occurred in the 1970s and 1980s, when PET decreased in the humid climate zone and increased in the semi-arid climate zone. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…At the beginning of the 21st century, Shi et al proposed that since the 1980s, the climate in the arid areas of Northwest China has gradually transformed from "warm and dry" to "warm and wet" [6]. Since then, scholars have conducted extensive research on the characteristics, formation mechanism, and future trends of climate warming and humidification in Northwest China [7][8][9][10][11][12][13]. Chen et al showed that the temperature and Atmosphere 2023, 14, 1421 2 of 12 precipitation in the arid region of Northwest China had "sharply" increased in the past 50 years.…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning of the 21st century, Shi et al proposed that since the 1980s, the climate in the arid areas of Northwest China has gradually transformed from "warm and dry" to "warm and wet" [6]. Since then, scholars have conducted extensive research on the characteristics, formation mechanism, and future trends of climate warming and humidification in Northwest China [7][8][9][10][11][12][13]. Chen et al showed that the temperature and Atmosphere 2023, 14, 1421 2 of 12 precipitation in the arid region of Northwest China had "sharply" increased in the past 50 years.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, evapotranspiration is not only an important part of the land water cycle, but also an important part of the land surface energy balance [3]. Moreover, both potential evapotranspiration (ET p ) and actual evapotranspiration (ET a ) had positive responses to temperature [4,5] and water vapor, which returns to the atmosphere through evapotranspiration and is also a major greenhouse gas capable of warming the climate [6]. Reasonable estimation of evapotranspiration is of great significance to regional climate change research [7], the rational utilization of water resources, agricultural irrigation, and water conservation projects [8].…”
Section: Introductionmentioning
confidence: 99%